The Noisy Oscillator : the First Hundred Years, From Einstein Until Now. - Gitterman, Moshe (World Scientific, 2005)
Stochastic Processes; Fluctuation Phenomena; Classical Statistical Mechanics; Oscillator; Brownian Motion; Stochastic Resonance; Multiplicative Noise.